Ritual, religion and reason: studies in the ancient world in honour of Paolo Xella - Loretz, Oswald; Xella, Paolo; Ribichini, Sergio; Watson, Wilfred G. E. 20./21. Jh.; Zamora, José Á. (Alter Orient und Altes Testament, 2013)
Literaturangaben und Indices